Rinoplastias: experiencia de un año en el departamento de otorrinolaringología del Hospital Clínico Universidad de Chile - Gutiérrez C., Daniela; Alzérreca A., J. Eugenio; Naser N., Alfredo; Zúñiga P., Jorge (Revista Hospital Clínico Universidad de Chile, 2011)
Rhinoseptoplasty is a surgical procedure performed by otolaryngologists, that solves aesthetic and functional problems of the nose as a sole surgery. It can be performed as an open or closed approach either with or without the use of implants and or grafts. We hereby show a retrospective analysis of surgical protocols of patients on whom rhinoseptoplasty was done in our Unit during 2010. Epidemiological data, surgical techniques, surgical time, management of the tip and dorsum, grafts used and complications were analized. 111 rhinoseptoplasties were performed. 14 were excluded due to lack of information in the files. From 97 patients included in the study, 54% were female, mean age 29, and 46% were male, mean age 28 years. The 82% consulted for nasal obstruction. 95% were primary rhinoplasties. 54% were approached by open technique and 46% by closed technique. 73% needed nasal tip management, and in 94% nasal dorsum surgery was performed. Grafts were used in 84% of cases, being the columellar strut preferred by the surgeon. There were no complications recorded. We conclude that this surgery was performed in a homogeneous way, mostly in patients with nasal obstructive symptom. There was a predominance of primary surgery with an extensive use of grafts.